HLJK-Info (Leuven: Homo- en Lesbienne Jongeren Koepel)
"Fonds Suzan Daniel (FSD)Periodiciteit : tweemaandelijksRedactie : Dambruggenstraat 204, 2060 Antwerpen ; vanaf 03(1992) 1 : Lange Leemstraat 337, 2018 Antwerpen"